FOSTERING RELIGIOUS HARMONY THROUGH ISLAMIC BOARDING SCHOOLS AT ISLAMIC BOARDING SCHOOLS DARUSSHOLAH IV AND DALILUL KHOIROT AN-NAWAWI BANGKA BELITUNG - Dewi, Ratna; Ansori, Muslim (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2023)
Abstract: This research aims to find out the fostering of religious harmony, the values of harmony and the obstacles faced by religious people through pesantren in Darussholah IV and Dalilul Khoirot An-Nawawi Islamic boarding schools in Bangka Belitung. This research is a descriptive qualitative research using a phenomenological approach. The results of this study are: cooperation in religious activities, as well as cooperation in social service activities. While the values of religious harmony are: the value of unity, ta'aruf", the value of equality of degrees, the value of tawheed, especially tawheed uluhiyah (tawheed of worship), the pledge of rejection of all forms and practices of worship to other than Allah and the value of faith. While the obstacles are: not wanting to be friends with close residents, there are some groups of people who argue with each other over matters of belief so that they want to be right themselves and who often idolize other groups, lack of knowledge and understanding of religion, negligence between together with the people so that the formation of conflict and mutual suspicion.Keywords : Coaching, Religius Harmony, Islamic Boarding School.